Pengaruh Perilaku Oportunistik, Asimetri Informasi, Moralitas Manajemen dan Kesesuaian Kompensasi Pada Praktik Kecurangan Akuntansi - Dwi Prawitasari, Ni Made; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi; Vol 28 No 3 (2019), 2019)
The purpose of this study was to look at the effect of opportunistic behavior, information asymmetry, management morality, and compensation suitability for accounting fraud practices in the Regional Government of Jembrana Regency. This research was conducted at the Jembrana Regional District Government. The number of samples taken was 108 people, using the purposive sampling method. The data analysis technique used is multiple linear regression analysis. Based on the results of multiple linear regression analysis found that high opportunistic behavior and high information asymmetry increase the occurrence of accounting fraud in the Jembrana Regency OPD. However, the better suitability of compensation will reduce accounting fraudulent behavior. Keywords : Opportunistic behavior, information asymmetry, management morality, conformity compensation.